Etika Teleologi dan Implikasinya dalam Praktek Administrasi Publik - Pontoan, Karen Alfa; Loho, Ambrosius M. (Indo-MathEdu Intellectuals Journal, 2025)
Every government needs a solid foundation. According to the author, this foundation is a crucial element, as it serves as a determinant in every policy taken by stakeholders. Success in carrying out public administration duties will be realized if it is based on a strong foundation, namely ethics. This article aims to explain and provide an analysis that ethics in public administration plays a major role in every public policy taken by decision-makers. The analytical descriptive method will be the model approach in this research. The results of the data analysis indicate that ethical values in public administration refer to basic moral principles such as integrity, honesty, transparency, accountability, fairness, and professionalism, which aim to create good governance by prioritizing the public interest, equality, and social justice.